Problems of Assessing Speaking as a Second Language - Israilova, Dildora; Karimova, Jamila (International Journal of Psychosocial Rehabilitation, 2020)
This article is devoted to the innovative methods of teaching English and assessing speaking in the B1-level students’ knowledge in non-philological higher educational systems.